Reef Fish Status in Northern Acehnese Reef Based on Management Type - EDI RUDI; SAYYID AFDHAL ELRAHIMI; TASRIF KARTAWIJAYA; YUDI HERDIANA; FAKHRIZAL SETIAWAN; SHINTA T. PARDEDE; STUART J. CAMPBELL; JERKER TAMELANDER (Biodiversitas Journal of Biological Diversity, 2009)
The objectives of this study were to provide reliable data and information on reef fish in the northern Aceh region of Wehand Aceh islands based on management types. This research use underwater visual census techniques at 29 sites aroundWeh Island and Aceh Islands. Reef fish abundance in area that were protected under the management of Panglima Laot ofSabang Weh Island (32505 no.ha-1) and biomass (748 kg.ha-1) were also significantly higher than in Aceh Islands which is open access areas (abundance=9539 no.ha-1; biomass=396 kg.ha-1). Fish species from the family Pomacentridae (damsel fish) were highest in abundance and biomass at northern Acehnese reef. Population of carnivorous fish such as parrotfish (Family Scaridae) was low in all study sites which indicated that northern Acehnese reef is lack of reef resilience both in managed and open access area. Higher numbers and abundance of reef fish in marine managed areas, such as Panglima Laot in Sabang, could be considered for further conservation purpose of marine resources.Key words: Coral reef, reef fish, management type, northern Acehnese reef